Proteomics studies of neurotoxic amyloid β oligomers using size exclusion chromatography - Das, Anuj Kumer (2012)
The prime toxic species that causes Alzheimer’s disease is believed to be oligomeric aggregates of the amyloid β peptide (Aβ). The major aim of the work was to develop methods to study which proteins in human plasma that interacts with oligomeric neurotoxic forms of Aβ. The interactions of Aβ with human biological fluid proteins are important for drug discovery efforts against Alzheimer’s disease but still not very well explored. Stable peptide oligomers were formed by a special variant of Aβ (called Aβ42cc). The co-elution of Aβ42cc oligomers with human blood serum was carried out using size exclusion chromatography (SEC). The eluted fractions were analyzed by SDS-PAGE but no strong interaction between Aβ oligomers and blood serum proteins could be observe.